A silver transformation: Chinese monetary integration in times of political disintegration, 1898–1933. (13th February 2020) - Ma, Debin; Zhao, Liuyan
Abstract: This article provides the first systematic econometric study on the evolution of Chinese silver exchange and monetary regimes during the period 1898–1933. Using high‐quality datasets of monthly and daily prices of silver dollars, we apply the threshold autoregressive models to estimate the silver points between Shanghai and 18 other cities in northern and central China. We find a noticeable improvement in monetary integration between Shanghai and Tianjin from the 1910s, which then spread to other cities in our sample throughout the 1920s and 1930s. We supplement our analysis with new datasets on volumes and costs of silver flows and with an in‐depth historical narrative. This article re‐evaluates the efficiency of the silver regime and China's economic performance in the Republican era.